Energy-efficient, scalable and modular industrial microwave applicator for high temperature alkaline hydrolysis of PET - Ramopoulos, Vasileios (Karlsruher Forschungsberichte aus dem Institut für Hochleistungsimpuls- und Mikrowellentechnik, 2023)
Microwave-assisted alkaline hydrolysis of PET can be 20 times faster and at lower temperatures. This work presents a novel industrial microwave applicator at 2.45 GHz with homogeneous distribution to support this reaction, which allows an efficient and continuous operation. In addition, an innovative dielectric and calorimetric measurements setup is presented. Furthermore, the modelling of the reaction kinetics based on the measured dielectric parameters is presented.